2011
DOI: 10.1007/s10646-011-0691-4
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of non-target invertebrates to Brazilian microbial pest control agents

Abstract: Microbial pest control agents or entomopathogens have been considered an interesting alternative to use instead of chemical insecticides. Knowledge of ecotoxicity data is very important to predict the hazard of any product released in the environment and subsidize the regulation of these products by governmental agencies. In the present study four new Brazilian strains of Bacillus and one fungus were tested to evaluate their acute toxicity to the microcrustacean Daphnia similis, the snail Biomphalaria glabrata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The elimination rate is an important parameter and needs to be included in microbial toxicity guidelines because this evaluation with entomopathogens is similar to the bioaccumulation factor for chemicals. As shown in other publications, Bacillus thuringiensis and B. sphaericus in the concentration of 10 6 spores/mL were not lethal to Biomphalaria glabrata (Oliveira-Filho et al 2011) or to the fish Danio rerio (Grisolia et al 2009). In the present study it was observed that the tested entomopathogens were not acutely toxic to Hyphessobrycon eques either.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The elimination rate is an important parameter and needs to be included in microbial toxicity guidelines because this evaluation with entomopathogens is similar to the bioaccumulation factor for chemicals. As shown in other publications, Bacillus thuringiensis and B. sphaericus in the concentration of 10 6 spores/mL were not lethal to Biomphalaria glabrata (Oliveira-Filho et al 2011) or to the fish Danio rerio (Grisolia et al 2009). In the present study it was observed that the tested entomopathogens were not acutely toxic to Hyphessobrycon eques either.…”
Section: Resultssupporting
confidence: 82%
“…Microbial pesticides have been presented as an alternative to chemical pesticides. Several studies have shown significantly higher efficiency and selectivity of Brazilian entomopathogens, which generate a lower environmental impact (Oliveira-Filho 2005;Grisolia et al 2009;Oliveira-Filho et al 2011). The use of microbial products for mosquito control has also been of great importance to developing countries, where the return of diseases transmitted by mosquitoes has become a public health problem in recent years (Sabbatini et al 2010).…”
mentioning
confidence: 99%
“…Reports in the literature have shown mortality of fish species Hyphessobrycon scholzei exposed to B. thuringiensis strain 344; however, the exposure concentration occurred at 1,0009 higher than that used in the field (Jonsson et al 2009). In contrast, B. thuringiensis did not cause any kind of toxic adverse effects to different fish species exposed to 1.3 and 1.7 9 10 10 spores (Johnson and McGaughey 1996) or up to 10 6 -10 7 spores/ml to freshwater invertebrates (Oliveira-Filho et al 2011).…”
Section: Resultsmentioning
confidence: 73%
“…(27). These authors studied the influence of pest control agents on nontarget invertebrates in soil.…”
Section: Statistical Approaches and Real Datamentioning
confidence: 99%
“…; Oliveira‐Filho et al. ; Yamamori ). It is important to state that the experimental design (e.g., the field lay‐out, sample size, sampling method, number of (sub) samples, and replicates, and the way in which the treatments are randomized over the experimental units) defines how the data should be analyzed.…”
Section: Introductionmentioning
confidence: 99%